SOSIAL EKONOMI, KONSUMSI FAST FOOD DAN RIWAYAT OBESITAS SEBAGAI FAKTOR RISIKO OBESITAS REMAJA[Socio-Economic, Fast Food Consumption and Obesity History as A Risk Factors of Adolescent Obesity] - Rifai Ali; Nuryani Nuryani (Media Gizi Indonesia, 2018)
Obesity is a public health problem that encompasses life cycle including adolescent. Adolescent obesity bring consequences to increase case of obesity in adult and the risk factors for degenerative diseases. This study analyze risk factor of socio-economic, parents history of obesity, nutrition knowledge and fast food consumption with the prevalence of adolescent obesity. The study was case control study and conducted at several high school in Gorontalo City, with 670 adolescent, consisting of 335 case groups and 335 control groups. Data analysis was performed to assess the risk of independent variables of obesity. Low father’s education (OR= 2.724; 95% CI; 1.970 – 3,767), low mother education (OR= 4.727; 95% CI; 3.357 – 6.657), parents history of obesity (OR= 2.016; 95% CI; 1.482 – 2.743), low adolescent knowledge (OR= 6.673; 95% CI; 2.296 – 19.393) and fast food consumption more than 3 times per week (OR= 1.829; 95% CI; 1.337 – 2.502) increasing the risk of adolescent obesity. Mother occupation as a household mother (OR=0.338; 95% CI; 0.224 – 0.468) become protective factor. Pocket money (OR= 1.015; 95% CI; 0.724 – 1.423) was not a risk factor of obesity. Multivariate analysis showed that mothers occupation was dominant factor that infl uence obesity. Parent education, history of obesity, nutrition knowledge and fast food consumption were risk factors for obesity.